2022
DOI: 10.1002/lio2.755
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroiditis in patients with sudden sensorineural hearing loss

Abstract: Objective This study aims to evaluate the association between autoimmune thyroiditis and Sudden Sensorineural Hearing Loss (SSNHL). Methods Hundred and five patients with SSNHL were enrolled. Audiometric tests, serum thyroid autoantibodies (TPOAb, TgAb) were studied. Based on the thyroid autoantibody results, patients were divided into two groups: thyroid autoantibody‐positive and negative. The relationship between thyroid autoimmunity and audiological characteristics was analyzed. Results Twenty‐six patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…For patients with SSNHL with a decline in middle to high frequencies, the pathogenesis is typically associated with damage to outer or inner hair cells. The distribution of ion channels on the basilar membrane of the cochlea differs in these patients, with more basal turn ion channels than apical turn ones, and may even be accompanied with localised vascular supply disturbances in the spiral ligament and hypoxia-induced damage to the spiral organ[ 11 ]. From this perspective, clinical recommendations suggest the use of glucocorticoids for treatment because they possess multiple effects, such as anti-inflammatory, immunosuppressive and antiallergic actions.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with SSNHL with a decline in middle to high frequencies, the pathogenesis is typically associated with damage to outer or inner hair cells. The distribution of ion channels on the basilar membrane of the cochlea differs in these patients, with more basal turn ion channels than apical turn ones, and may even be accompanied with localised vascular supply disturbances in the spiral ligament and hypoxia-induced damage to the spiral organ[ 11 ]. From this perspective, clinical recommendations suggest the use of glucocorticoids for treatment because they possess multiple effects, such as anti-inflammatory, immunosuppressive and antiallergic actions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, diabetes mellitus, and hyperlipidemia are risk factors for SSNHL's poor prognosis (10,12), and abnormal thyroid function has been correlated with the development of SSNHL (13). Meanwhile, the onset of hypertension and diabetes is closely associated with age, and blood indices such as bilirubin and 15).…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for possible influencing factors such as age, concomitant symptoms, cardiovascular inflammatory markers, and audiograms, we found that hearing at 8,000 Hz mainly affects the prognosis of SSNHL. Several studies have shown that when vascular, endocrine and immune dysfunction accompany hearing loss, high-frequency hearing impairment first appears, of which 8,000 is common (40)(41)(42)(43)(44)(45). In a per-frequency predictive model, highfrequency hearing loss in SSNHL patients was more difficult to recover than other frequencies, and this correlation was more pronounced at 8,000 Hz (46).…”
Section: Discussionmentioning
confidence: 99%